Power optimization control of VSC-HVDC system for electromechanical oscillation suppression and grid frequency control - Bi, Chaohao; Wu, Jiaqi; Qian, Yang; Luo, Xin; Xie, Jianxiang; Shi, Jianquan; Luo, Fang (Frontiers in Energy Research, 2022)
The voltage source converter (VSC) based high-voltage DC (HVDC) transmission system usually adopts damping and inertia control to quickly and independently adjust the active- and reactive- power, to improve the frequency stability and suppress the electromechanical oscillations of the power grid. This paper first analyzes the effect of the proportional-derivative (PD) controller parameter on the HVDC output power. The study shows that when the proportional-derivative controller parameter is increased to the limit value, HVDC will operate in the rapid power compensation (RPC) mode. Namely, according to the positive or negative polarities of the rotor speed deviation and the grid frequency deviation, the active- and reactive- power limits are used as the reference to rapidly control the output power, thereby minimizing the system’s unbalanced power, the rotor oscillation, and the frequency fluctuation. To this end, this paper proposes a coordinated active-/reactive- power control strategy for the VSC-HVDC system based on the RPC mode to suppress the grid electromechanical and frequency oscillations. The RPC mode enables HVDC to quickly release/absorb power, to compensate for system’s required power shortage or suppress excess power. When the speed deviation, the frequency deviation, and their rates of change meet the requirements, the damping control is used to make HVDC exit the RPC mode and further enhance the ability of the VSC-HVDC system. Simulation results prove the effectiveness of the proposed power optimization control strategy.